ANALYSIS RECEPTION LOCAL TAX BEFORE AND AFTER USE TAPPING BOX - Wulan Nurhasanah; Elan Eriswanto; Hendra Tanjung (Scholars Digest Publishing, 2023)
Tapping Box is a device that is installed on a cash register which aims to monitor every transaction transactions that occur at the place of business. This study aims to find out how the application of tapping box, know reception tax area before And after use tapping box. Study This using qualitative methods with a descriptive approach. Data collection techniques use data primary includes observation, interviews, and documentation, secondary data includes reports on tax targets and realization restaurant, hotel tax, parking tax and entertainment tax, annually during the period 2017-2022. The results of this study showing that until year 2022 device tapping box Already applied as much 40 device on must taxes in Sukabumi City, only the accuracy of the data generated is not 100% accurate. before using tapping box tax area in City Sukabumi Already runs well every the year However there is tax Which No reached the target, namely the hotel tax and entertainment tax in 2017. After using the tapping box experienced a significant increase from before using tapping boxes, but on entertainment taxes and tax parking income decrease on year 2021 consequence impact covid-19.
Keywords: Tax, Tax Area, tapping box.